Innovation in physical education: The role of cognitive factors and self-efficacy - Li, Songpu; Xu, Ruilin; Zhao, Zijian (Frontiers in Psychology, 2022)
Among the beliefs related to teaching work, self-efficacy stands out and encourages innovation across the global education systems. Specifically, the lack of interest among instructors in introducing innovative techniques in physical education is a concern across China. Therefore, this study intends to investigate the role of cognitive indicators (Mental Workload, Decision Making Process & Intentions) and Self Efficacy) of innovation in physical education across China. The study opted for quantitative techniques, including using a structured questionnaire to collect data from targeted respondents through the survey techniques. Moreover, 800 questionnaires were circulated, and as a result, 420 usable responses were attained, making the overall response rate stood at 40%. The results indicate that the above-stated cognitive factors, along with self-efficacy, have a positive role in causing innovation across the physical education exchequer of China. Likewise, Self-efficacy played the mediating role between Cognitive indicators and innovation in physical education in China. The study has notable theoretical and practical implications for the policymakers in terms of introducing policies that could help increase the cognitive state of educationists, which in turn possibly will help make them pursue innovation within the education system of China.